Clinicopathological Profile of Colorectal Cancer Patients at Dr. Zainoel Abidin General Hospital, Banda Aceh, Indonesia: A Single-Center Retrospective Study - Nanda Subhan; Khalikul Razi; Maria Meildi; Darul Ilham; T. Fenny Novhera (Journal of Society Medicine, 2026)
Introduction: Colorectal cancer (CRC) is a major global malignancy and a growing issue in Southeast Asia, with limited data from Indonesian hospitals outside Java. This study described demographic, anatomical, pathological, staging, and surgical characteristics of CRC patients at Dr. Zainoel Abidin General Hospital, Banda Aceh, in 2024. Methods: This retrospective study reviewed records of histopathologically confirmed CRC patients treated between January and December 2024. Incomplete records were excluded. Variables included age, sex, tumor location, AJCC stage, histological subtype, and surgical procedure. Continuous variables are mean ± standard deviation; categorical variables are frequencies and percentages with 95% confidence intervals. Statistical comparisons used chi-square goodness-of-fit, one-sample t-test, and proportion tests, with p < 0.05 significant. Results: Fifty-seven patients were included. Mean age was 49.37 ± 12.4 years, significantly younger than the global reference of 60 years (p < 0.001). Most were aged 46–65 years (57.9%), with males slightly predominating (54.4%). The rectum was the most common tumor site (56.1%), and stage III was most frequent (40.4%). Advanced-stage disease (stage III–IV) was observed in 52.6%. Adenocarcinoma accounted for 91.2%. Open laparotomy was the most common surgical approach (70.2%), followed by abdominoperineal resection, low anterior resection, and Hartmann procedure. Conclusion: CRC patients at RSUDZA in 2024 presented younger, with rectal predominance, frequent advanced-stage disease, and a dominance of open surgery, highlighting the need for earlier detection and surgical capacity in Aceh, Indonesia.